Debt, equity, and capital investment - Jackson, Scott B.; Keune, Timothy M.; Salzsieder, Leigh (Journal of Accounting and Economics, 2013)
Theory suggests that debt financing, relative to equity financing, makes managers reluctant to part with assets. Our evidence supports this theoretical prediction, revealing that the reluctance to part with a debt financed asset causes two decision errors—(1) participants forego investments that increase firm value and (2) participants accept investments that decrease firm value. When the source of finance is equity, participants are less likely to make either of these costly decision errors. Further, we find that higher unpaid principal accentuates participants' reluctance to part with debt financed assets. Finally, the decision errors stem, in part, from the perception that an asset having a large unpaid principal balance has provided lower past benefits than an otherwise identical asset.